The toxic effect of cytostatics on primary cilia frequency and multiciliation. Issue 8 (17th June 2019) - Filipová, Alžběta; Diaz Garcia, Daniel; Bezrouk, Aleš; Čížková, Dana; Dvořák, Josef; Filip, Stanislav; Sturge, Justin; Dayanithi, Govindan; Šinkorová, Zuzana
Abstract: The primary cilium is considered as a key component of morphological cellular stability. However, cancer cells are notorious for lacking primary cilia in most cases, depending upon the tumour type. Previous reports have shown the effect of starvation and cytostatics on ciliogenesis in normal and cancer cells although with limited success, especially when concerning the latter. In this study, we evaluated the presence and frequency of primary cilia in breast fibroblasts and in triple‐negative breast cancer cells after treatment with cytostatics finding that, in the case of breast fibroblasts, primary cilia were detected at their highest incidence 72 hours after treatment with 120 nM doxorubicin. Further, multiciliated cells were also detected after treatment with 80 nM doxorubicin. On the other hand, treatment with taxol increased the number of ciliated cells only at low concentrations (1.25 and 3.25 nM) and did not induce multiciliation. Interestingly, triple‐negative breast cancer cells did not present primary cilia after treatment with either doxorubicin or taxol. This is the first study reporting the presence of multiple primary cilia in breast fibroblasts induced by doxorubicin. However, the null effect of these cytostatics on primary cilia incidence in the evaluated triple negative breast carcinomas cell lines requires further research.